By Chance or by Plan?: The Academic Success of Nontraditional Students in Higher Education - Billy Wong (SAGE Publishing, 2018)
In the United Kingdom, a "good" undergraduate degree is understood to be a "first class" or an "upper second class," which is achieved by three-quarters of students. The need to distinguish oneself from others is ever more important in an increasingly crowded graduate market, although a first-class degree is most likely achieved by privileged students. Informed by Bourdieu's theory of habitus and capital, this study explores the educational experiences and trajectories of 30 final-year high-achieving nontraditional (HANT) students through in-depth interviews. These include working-class, minority ethnic, and/or mature students at university. We found that prior development in academic study skills and the desire to prove oneself, often in response to previous negative experiences, are key ingredients in academic success. Our HANT students also seem to find inspiration or support from significant others, an educational capital, although these resources are often by chance rather than by plan. Implications for policy and practice are suggested.